Perancangan Aplikasi Virtual Reality Bangun Ruang Dengan Menggunakan Aplikasi Blender Dan Unity 3D - Ardhana, Fahri; Khair, Ummul; Khairani, Mufida (Universitas Harapan Medan, 2023)
Virtual Reality (VR) applications have become a technology that has become increasingly popular and developed rapidly in recent years. Virtual Reality allows users to experience and interact with immersive and immersive virtual environments. One interesting use of Virtual Reality is in learning geometric shapes (blocks, cubes and balls). Learning to build space usually only takes the form of pictures which are limited to teaching materials, either books or modules. The Blender and Unity 3D applications can be used in designing virtual reality building applications. Blender is a powerful open source software for 3D modeling and animation.